(3GdNUNUI(B-(3GdYhdeI(B-(3GdGbJUGO GdeYQajs - (3eMeO GHQGgje(B, (3YHO GdQMjes ((3GdGScfOQjI(B:s (3eDSSI THGH GdLGeYI(B,s, 2007)
(3jJfGhd GdcGJH aj GdbSe GdGhd GdNUNUI hfXQI Mhd Jbjje GdbWGY GdYGe GdUfGYj GdNUNUI hMhGaR GdHGdhf, heGPG HYO GdNUNUI, GdNUNUI hJSYjQ GdGUhd , CSGdjH JSYjQ hJbjje GdTQcGJ, Jbjje GdGUhd GdZjQ edehSI hTgQI GdeMd (B.(3GdNUNUI hYbO GdJfejI GdVGFY, OhQ GdeLJeY GdOhdj dfLGM GdNUNUI ceG JfGhd aj GdbSe GdKGfj GdYhdeI hYhdeI QCS GdeGd GdUfGYj hGdJcfhdhLjG , GdJObjb hGdaSGO GdeGdj GdYGdej, GdGReGJ GdeGdjI hWffI YhdeI Ge GeQcI GdeOjhfjI aj efXhQ GdGYJeGO Ydj GdPGJ, CKQ VQjHI GdWGbI Ydj GdGSJJeGQ GdUfGYj ceG JWQb aj GdbSe GdKGdK (B((3ef GdGbJUGO GdUfGYj Gdj GdGbJUGO GdeYQaj(B) (3h GdUfGYGJ GdUZjQI Hjf GdMde hGdhGbY, GdUfGYGJ GdUZjQI hGdGSJQGJjLjI GdGYfeGO Ydj GdOGJ, OhQ GdUfGYGJ GdUZjQI aj GdUGOQGJ GdUfGYjI, Jbjje UdGMjI LOhj GdeTQhY, UGaj GdbjeI GdMGdjI heYOd GdYGFO HGSJeQGQ, JMOjJ GdUfGYI, GdUfGYI h GdJcfhdhLjG, fXQI Mhd GdGbJUGO GdeYQaj(B.s
(3HjHdjhZQGajG(B: (3U(B.201s
Keywords: (3GdbWGY GdNGUs; (3GdeDSSGJ GdYGeIs; (3YhdeIs